Der schwierige Weg zum Westfälischen Frieden Wendepunkte, Friedensversuche und die Rolle der "Dritten Partei" - Arnke, Volker 1982-; Westphal, Siegrid 1963- (bibliothek altes Reich, 2021)
Before the group of imperial delegates often referred to as "Third Parties" definitively brought about the signing of the Peace of Westphalia in 1648, numerous earlier attempts to end the Thirty Years War or to prevent it had failed. The volume examines key turning points, including the outbreak of war, failed attempts to restore peace, and the ultimate conclusion of the conflict